Pendampingan Sebagai Upaya Optimalisasi Literasi Digital dan Pengelolaan UMKM melalui Implementasi Pembelajaran Digital Marketing - Inas Sany Muyassaroh; Ike Desi Florina; Sherly Adinda Apriliani; Zahra Marsha Nabila (Jurnal Pengabdian Masyarakat Waradin, 2024)
Developing micro, small, and medium enterprises (M.S.M.E.s) in Tegal City supports local and national economic growth. However, many M.S.M.E.s need help understanding and utilizing digital marketing, which is increasingly essential in today’s digital era. This study aims to improve the digital marketing capabilities of M.S.M.E.s in Tegal City through a mentoring program involving communication science students. The methods include preparation, research, analysis, program implementation, evaluation, and activity reports. This program involves students supporting M.S.M.E.s, including creating social media and content and managing e-commerce accounts. The study results show that this mentoring has succeeded in increasing the visibility of M.S.M.E. products and expanding market reach. The implementation of digital marketing strategies assisted by students has a significant impact on the sustainability and competitiveness of M.S.M.E.s in Tegal City.